Numerical study of thermal lensing and focal shift in 1064~nm fiber laser cutting heads 1-6 kW - Thanh Tung, Do (Communications in Physics, 2025)
Thermal lensing is an unavoidable phenomenon in optical systems utilizing high-power lasers, including laser cutting heads, due to energy absorption-induced thermal and optical variations. This study analyzes its effects on a 1064 nm laser system (1–6 kW) using two fused silica plano-convex lenses, with focusing lens focal lengths of 125–300 mm. Simulations indicate a peak lens temperature of 952 K at 6 kW, driving focal shifts up to Δf = −45.4 mm (300 mm focal length) and relative refractive index changes of 74.5–114%. Spot diagram analysis at the focal plane indicates severe beam spreading and optical distortion when the laser power exceeds 4 kW. Proposed solutions include thermally stable materials, enhanced anti-reflective coatings, and real-time focal adjustments to optimize cutting precision.